GENDERAN ADA-ADA GAYA NYI SUWANDA DALAM SAJIAN WAYANG KULIT PURWA GAYA YOGYAKARTA - Suharjono; Aji Santosa Nugroho; Siswati Siswati (Surakarta: Jurusan Karawitan Institut Seni Indonesia Surakarta, 2025)
This study was conducted to find out and explore the techniques, patterns and dynamics of genderan ada-ada wayang kulit purwa Yogyakarta style performed by Nyi Suwanda. In addition, this study is also a means of documenting genderan wayang kulit Yogyakarta style, especially female genderan. In ancient times, especially in the puppetry environment, genderan wayang was generally performed by female genderan. However, along with the progress of the era and the development of karawitan, there has been a shift with the emergence of male genderan in pakeliran karawitan. The uniqueness of the female genderan style of Nyi Suwanda, it is important to document in writing, with the aim that it can be known and studied by the next generation. Thus, the history of genderan wayang originating from female genderan is not interrupted. The research method used is descriptive analysis. The analysis is carried out through several stages, namely: observation by listening to recordings, participatory observation of transcription, identification of techniques, patterns, dynamics and drawing conclusions. Based on the analysis conducted, this study successfully obtained several findings regarding the elements of technique, pattern, dynamics, and laya performed by Nyi Suwanda in the presentation of ada-ada wayang kulit purwa in the style of Yogyakarta. The elements of technique that were successfully found included gembyungan and pipilan. The elements of pattern found included kawitan, baku, rambatan, and panutup. The elements of dynamics found included hard and lirih, while the elements of laya were found to tend to be magak (steady) and firm.